A novel implantable catheter system with transcutaneous port for intermittent convection-enhanced delivery of carboplatin for recurrent glioblastoma. (2nd January 2016) - Barua, Neil U.; Hopkins, Kirsten; Woolley, Max; O'Sullivan, Stephen; Harrison, Rob; Edwards, Richard J.; Bienemann, Alison S.; Wyatt, Marcella J.; Arshad, Azeem; Gill, Steven S.
Abstract: Context : Inadequate penetration of the blood–brain barrier (BBB) by systemically administered chemotherapies including carboplatin is implicated in their failure to improve prognosis for patients with glioblastoma. Convection-enhanced delivery (CED) of carboplatin has the potential to improve outcomes by facilitating bypass of the BBB. Objective : We report the first use of an implantable CED system incorporating a novel transcutaneous bone-anchored port (TBAP) for intermittent CED of carboplatin in a patient with recurrent glioblastoma. Materials and methods : The CED catheter system was implanted using a robot-assisted surgical method. Catheter targeting accuracy was verified by performing intra-operative O-arm imaging. The TBAP was implanted using a skin-flap dermatome technique modeled on bone-anchored hearing aid surgery. Repeated infusions were performed by attaching a needle administration set to the TBAP. Drug distribution was monitored with serial real-time T2-weighted magnetic resonance imaging (MRI). Results : All catheters were implanted to within 1.5 mm of their planned target. Intermittent infusions of carboplatin were performed on three consecutive days and repeated after one month without the need for further surgical intervention. Infused volumes of 27.9 ml per day were well tolerated, with the exception of a single seizure episode. Follow-up MRI at eight weeks demonstrated a significant reduction in the volume of tumor enhancement from 42.6 ml to 24.6 ml, and was associated with stability of the patient's clinical condition. Conclusion : Reduction in the volume of tumor enhancement indicates that intermittent CED of carboplatin has the potential to improve outcomes in glioblastoma. The novel technology described in this report make intermittent CED infusion regimes an achievable treatment strategy.